FAKTOR PENENTU INDUSTRI RUMAH TANGGA GULA AREN MEMPERTAHANKAN USAHANYA DI KECAMATAN AIR PERIUKAN - Manik, Frans Valentino; Fariadi, Herri; Nurmalia, Ana (University of Prof. Dr. Hazairin, SH, 2024)
Palm sugar household industry becomes a main income for people at Air Periukan Regency. But for years due to a lot of demands about changing palm water palm sap water into alcoholic drinks. There is a chance for producers to change their business, but they maintain their business to produce palm sugar. The purpose of this research is to find out the decision level of palm sugar producers in sustaining their household industry and to analyze the factors which decide palm sugar household industry to keep sustaining their industry. The method used in this research is quantitative research by using multiple linear regression. The result of this research shows that their decision in sustaining their industry have average score of 37,82 means their decision in sustaining the industry is in high category. Factors which influence the industry are social norm factor (X1), production cost (X3), revenue (X4), marketing (X5), product sustainability (X6) and experiences (X8) while the price stability fact (X2), production process (X7) isn't become decision factor.